Individual and neighborhood factors associated with being unvaccinated against COVID-19 among pregnant persons - Ousseny Zerbo; G. Thomas Ray; Bruce Fireman; Evan Layefsky; Kristin Goddard; Pat Ross; Mara Greenberg; Nicola P. Klein (Taylor & Francis Group, 2023)
We investigated whether unvaccinated pregnant persons cluster geographically and determined factors associated with being unvaccinated using spatial and multivariate logistic regression analyses. Pregnant persons with deliveries from December 15, 2020, through September 30, 2022, at Kaiser Permanente Northern California were included. Of the 85,852 pregnant persons in the study, 46.6% were unvaccinated before and during pregnancy. Spatial analysis identified 5 clusters with high prevalence of unvaccinated pregnant persons. Within these clusters, the proportion of unvaccinated varied from 53% to 62% versus 39% outside the clusters. In covariate-adjusted analyses, residence in a cluster increased the odds of being unvaccinated by 1.64 (95% confidence interval (CI): 1.59,1.69). The odds of being unvaccinated increased among those aged 16-24 years (odds ratio [OR] = 2.69, CI: 2.55, 2.83), aged 25-34 years (OR = 1.59, CI: 1.54, 1.64) compared with age ≥ 35 years, black race (OR = 1.45, CI:1.37, 1.54), and subsidized insurance (OR = 1.32, CI: 1.26, 1.38). The odds of being unvaccinated also increased for pregnant persons living in neighborhoods where the proportion of adults with high school education or less was greater than 20%. Geographic clustering of unvaccinated pregnant persons suggests a need for population-specific-interventions to increase vaccine coverage.